(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This bibliography represents the fourth sequel of the bibliography of magazines Ženski svet: list dobrotvornih zadruga Srpkinja [Women’s World: The Newsletter of Charity Cooperatives of Serbian Women]. It encompasses the five years in which the magazine was published, from 1899 to 1903 and contains 973 bibliographic units described with de visu language using the script of the publication. As in the previous bibliographies, the units are placed in alphabetical order, according to the author’s surname or the title of the article – when the texts were not signed or when initials were used. Since all units have been entered into the joint database, the COBISS.ID number was provided together with the categorization of the article. In accordance with informative requests, registers that separate the title, the author and the topic have been included.